Petri net based modelling and simulation of p16-Cdk4/6-Rb pathway - Akçay, Nimet İlke; Bashirov, Rza; Tüzmen, Şükrü (CEUR-WS, 2013)
Tumor suppressor gene p16 is of utmost interest in investigation of signal transduction pathways due to its gatekeeper role at the G1/S checkpoint of the cell cycle. Defects in p16 result in uncontrolled cell division which leads to progression of malignancy in an organism. In the present research we focus on p16-Cdk4/6-Rb pathway which is a cornerstone of G1 phase of the cell cycle. We implement Pet net formalism and Cell Illustrator software tool to create model of p16-Cdk4/6-Rb pathway and perform a series of simulations to validate the model.
4th International Workshop on Biological Processes and Petri Nets, BioPPN 2013 - A Satellite Event of PETRI NETS 2013 -- 2013-06-24 -- Milano -- 110541
Keywords: Cell cycle; Cell Illustrator; Hybrid functional petri net; P16-Cdk4/6-Rb pathway; Replicative senescence